Respiration and Carbon Dioxide Accumulation in Soil Microcosms - Jasity Murphy (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
The thawing of permafrost leads to liberation of soil organic matter and microbial component resulting in significant effect on the carbon cycle. Changes in permafrost soils upon the global climate warming would significantly impact microbial soil activity. Currently, not a great deal is known about what happens to the microbial community after the permafrost thaws. The activity of microbial community was determined in microcosms experiment using respirometry. To assess the CO2 fluctuations during permafrost thawing a titration experiment was performed. Based on calculations using the respirometric equation it was found that CO2 production increases with temperature, core depth, ion amendments and duration of time.
Keywords: Soil; Microbes